2011
DOI: 10.1007/s00464-011-1854-3
|View full text |Cite
|
Sign up to set email alerts
|

Near-infrared (NIR) laparoscopy for intraoperative lymphatic road-mapping and sentinel node identification during definitive surgical resection of early-stage colorectal neoplasia

Abstract: In this study, NIR laparoscopy with ICG mapping allowed ready and rapid confirmation of mesocolic lymphatic drainage patterns and sentinel node identification. With further validation, this technology and technique promises precise, tailored resection surgery by indicating basin pattern and status in advance of radical lymphadenectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
114
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(128 citation statements)
references
References 31 publications
5
114
0
1
Order By: Relevance
“…Quick switch of NIRF imaging facilitated the confirmation of mesocolic lymphatic drainage patterns and the identification of SLNs. 169 The aforementioned studies ascertain the effectiveness of NIRF imaging in clinical settings. NIRF imaging has been experiencing explosive development and will be employed in more operating rooms and other biomedical applications.…”
mentioning
confidence: 99%
“…Quick switch of NIRF imaging facilitated the confirmation of mesocolic lymphatic drainage patterns and the identification of SLNs. 169 The aforementioned studies ascertain the effectiveness of NIRF imaging in clinical settings. NIRF imaging has been experiencing explosive development and will be employed in more operating rooms and other biomedical applications.…”
mentioning
confidence: 99%
“…Several studies have found that the detection rate for sentinel nodes using ICG is relatively high [23, 25, 27-30]. The studies varied in their method of instilling the tracer, with some using laparoscopic insertion of the dye through the serosa and others using colonoscopic administration.…”
Section: Resultsmentioning
confidence: 99%
“…39 In turn, the increase in exposure times during NIR fluorescence detection resulted in low acquisition frame rates making this approach impractical for real-time ergonomic clinical use. Furthermore, the potential of NIR fluorescence-guided endoscopic imaging is highlighted by the development of commercial clinically compatible systems optimized for NIR fluorescence imaging (e.g., Storz FL series 40 and Novadaq spyscope 41 ). These systems are, however, either designed for single-channel imaging (i.e., either color or NIR), or present a significant amount of fluorescence background.…”
Section: Introductionmentioning
confidence: 99%